(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the study, we concentrated on the Uniqueness Theorems and Meromorphic Structure Deficiencies, Growth limitation regarding poles and zeros and meromorphic functions with non-zero subordinates and related polynomial differentials and Fix points normal and characteristic groups of some homogeneous polynomials. Additionally we study Angular conveyance of meromorphic functions concerning homogeneous and differential polynomials.